2019
DOI: 10.1242/dmm.041947
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of the microbiome, immune system, and epigenome with disease progression in ALS mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a terminal neurodegenerative disease. Genetic predisposition, epigenetic changes, aging and accumulated lifelong environmental exposures are known ALS risk factors. The complex and dynamic interplay between these pathological influences plays a role in disease onset and progression. Recently, the gut microbiome has also been implicated in ALS development. In addition, immune cell populations are differentially expanded and activated in ALS compared to healthy individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 113 publications
(162 reference statements)
2
63
0
Order By: Relevance
“…However, an increase in DNA methylation was found in the blood of ALS subjects, regardless of the time of onset of the disorder (Tremolizzo et al, 2014). Moreover, total cytosine hydroxymethylation has been found in the brains of end-stage SOD1 transgenic animals (Figueroa-Romero et al, 2019), while altered levels of DNA methylation have been reported in postmortem brains from sALS individuals when compared to age-matched controls (Morahan et al, 2009). Curiously, 60% of the genes affected by such changes are involved in neurotransmission, oxidative stress, and calcium handling, mechanisms that are thought to be disrupted in ALS (Morahan et al, 2009).…”
Section: Regulation Of Neurogenic Function In Als Through Epigenetic mentioning
confidence: 96%
“…However, an increase in DNA methylation was found in the blood of ALS subjects, regardless of the time of onset of the disorder (Tremolizzo et al, 2014). Moreover, total cytosine hydroxymethylation has been found in the brains of end-stage SOD1 transgenic animals (Figueroa-Romero et al, 2019), while altered levels of DNA methylation have been reported in postmortem brains from sALS individuals when compared to age-matched controls (Morahan et al, 2009). Curiously, 60% of the genes affected by such changes are involved in neurotransmission, oxidative stress, and calcium handling, mechanisms that are thought to be disrupted in ALS (Morahan et al, 2009).…”
Section: Regulation Of Neurogenic Function In Als Through Epigenetic mentioning
confidence: 96%
“…Although there is no direct evidence suggesting the efficacy of rofecoxib on treating ALS via inhibiting peripheral inflammation, activated macrophages, mast cells, and T cells have been confirmed to be responsible for inducing the inflammation in the spinal cords of ALS (Graves et al, 2004). Consistently, dysregulation of immune system has been reported in the spinal cord of SOD1 G93A mice (Figueroa-Romero et al, 2019). By the involvement of immune system in the pathogenesis of ALS, stimulating the protective effects of the immune system in humans, including intravenous immunoglobulins, and other experimental interventions such as antibodies, vaccination, minocycline, and neural stem cells have shown the promise efficacy on treating animal models of ALS (Chio et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…the vascular, and the nervous systems (Figure 2; Schroeder and Bäckhed, 2016;Cox and Weiner, 2018;Butler et al, 2019;Cryan et al, 2019). Modifications in the composition of the GM was reported in brain disorders, such as autism (Adams et al, 2011;Kang et al, 2019), depression (Kelly et al, 2016;Zheng et al, 2016), Parkinson's disease (Scheperjans et al, 2015;Sampson et al, 2016), and AD (Cattaneo et al, 2017;Vogt et al, 2017;Zhuang et al, 2018). Intriguingly, the extent of the amyloid pathology in AD mice appears to be dependent of the microbial status, which is specific to the animal housing facility.…”
Section: The Gut-brain Axis and Neurodegeneration: Is There A Barriermentioning
confidence: 99%